Customer service analysis with the overview of marketing and promotional activities of BRAC bank ltd. - Roy, Joydeep Sinha (BRAC University, 2011)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2010.